A REVIEW ON RECENT ADVANCEMENT IN PULSATILE DRUG DELIVERY SYSTEMS - THAKUR, GAURAV; WANI, SHAHID UD DIN; GAUTAM, SURYA PRAKASH (International Journal of Current Pharmaceutical Research, 2021)
Delivery systems with a pulsatile-release method are particularly involved in designing medicines for which traditional managed drug-release systems with the continuous release are not suitable. This medication also has a high first-pass impact or special conditions for chrono-pharmacology. These medications also have a high first-pass or unique chronopharmacological effect. The pulsatile release profile is characterised by a duration of no release (lag time) followed by a fast and full release of the drug. Pulsatile drug delivery systems may be classified into site-specific systems in which the drug is released inside the gastrointestinal system (e. g. colon) or time-controlled devices wherein the drug is released after a well-defined time period. Site-regulated release is typically controlled by environmental factors, such as pH or enzymes found in the intestinal tract, whereas drug release from time-controlled processes is controlled mainly by the delivery system and, preferably, not by the environment. This review covers various single-and multiple-unit oral pulsatile drug-delivery systems with an emphasis on time-controlled drug-release systems.